Analisis Literatur Implementasi Pembelajaran Seni Rupa Dalam Meningkatkan Apresiasi Siswa Sekolah Dasar - Fatimah Azzahra; Himatul Azka; Bintan Karima Faida; Salma Fitriani Novanda (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2026)
Fine arts education at the elementary school level is an important part of shaping students' personalities, aesthetic sensitivity, and creativity. However, several challenges remain, such as an over-focus on technical aspects, limited teacher competency, and inadequate facilities. The purpose of this study is to examine effective fine arts learning strategies and methods to enhance students' aesthetic appreciation. The research method used a literature review with a qualitative descriptive approach, analyzing the content of various related sources. The results show that the project-based learning approach, the use of creative media and local culture, and pedagogical art criticism are very effective in shaping students' appreciation. In general, the results of this study are important because they encourage innovation in the fine arts learning process, thereby shaping students' aesthetic character from an early age.